Research of crack initiation and propagation under loading for providing impact resilience of protective coating - Sapronov, O.O.; Buketov, A.V.; Marushchak, P.O.; Panin, S.V.; Brailo, M.V.; Yakushchenko, S.V.; Sapronova, A.V.; Leshchenko, O.V.; Menou, A. (Functional Materials, 2019)
The analysis of destruction process under the impact loading of developed epoxy composites with different content of carbon nanotubes is carried out. Introduction of nanoparticles into the epoxy binder at the optimal content of q = 0.010 pts·wt. allows 3 times increase of impact resilience relative to the epoxy matrix. The loading value at the moment of material destruction, the value of critical strain and the crack propagation rate in time to the materials destruction on the impact testing machine RKP-300 for high-speed loading are established. By the method of optical and electron microscopy it is established that the uniformity of particles distribution of carbon nanotubes influences the morphology of nanocomposites, and hence the properties of the formed materials.